The extended evolutionary synthesis and human origins: Archaeological perspectives. Issue 1 (23rd June 2020) - Murray, John K.; Benitez, Robert Acio; O'Brien, Michael J.
Abstract: Recent developments in evolutionary biology have led to a call for an extension of standard evolutionary theory, with its emphasis on processes such as selection and drift, into a much larger theoretical framework that includes processes such as niche construction, developmental plasticity, inclusive inheritance, and developmental bias. Skeptics argue that these processes are already subsumed within the standard theory and thus an extension is not required. Here, we outline what this evolutionary "rethink" might mean for the study of human origins. Specifically, can paleoanthropologists benefit from an extended theoretical toolkit? The papers in this special issue suggest it can be useful but may not be necessary, depending on the kinds of questions that are being asked.